Civic Deficit Among High School Students: A Qualitative Study of Constitutional Political Education in Public Schools - Rengga Yudha Santoso; Yohana Rosita Dewi Mariyani; Anisa Prastiwi; Ragil Putri Hari Kartini (Global Education Journal, 2026)
The shifting dynamics of global democracy have positioned civic education as a crucial pillar in shaping the civic engagement of the younger generation. This research aims to investigate the forms and causes of civic deficit among high school students in the context of constitutional political education. Using a qualitative approach with a case study design at SMA Negeri 1 Rejoso, Nganjuk, data was collected thru in-depth interviews with 4 Civics teachers and 30 students from class X, as well as document analysis of syllabi, lesson plans, and textbooks. Thematic analysis techniques were used to identify patterns in learning experiences, perceptions, and practices. The findings indicate that the civic deficit is not only rooted in students' lack of interest in political issues, but is also fueled by structural conditions within the education system, including pedagogical stagnation due to administrative pressure and inadequate welfare for contract teachers. Civics education tends to be monological, normative, and lacks local contextualization, leading to political alienation among students. Teaching materials that are merely an administrative formality reinforce this alienation. A curriculum unsupported by a well-being ecosystem and fair teacher distribution fails to create deliberative space in the classroom.